Review on survey of paediatric optometry practice / Nur Latifah Abdullah Zawawi - Abdullah Zawawi, Nur Latifah (2016)
Paediatric optometry was one of the many branches of optometry practice in which it focuses only on children from infant till school age. The priority of paediatric optometry is to ensure the children to receive full eye check-up from young age. This was because any early detection could lead to better prognosis for any children who had vision abnormalities, either by treating or decreasing the progress of the abnormalities detected. This study was to review the scopes in published surveys used to investigate the current practice of paediatric optometry among all the eye care practitioners and to propose scopes of the survey on comprehensive paediatric practice among eye care practitioner in Malaysia based on the review. All the existing surveys were obtained through search engine Science Direct, Wiley Online Library, Pub Med, Sage and Google Scholar .The keywords used were “paediatric”, “optometry”, “eye care practitioner”, “eye care services”, “vision screening”, “comprehensive eye examination” and “survey”. Out of 32 journals reviewed, 22 (68.8%) did not mention about the length of the survey while 10 (31.3%) mention the length of the survey. Among 32 journals, 17 (53.1%) were distributed by mail, 3 (9.4%) were distributed by email, 11 (34.4%) were based on interview and 1 (3.1%) by mail and email. The number of journals that targeted the eye care practitioners was 9 (28.1%) which were distributed among optometrists, another 9 (28.1%) were distributed among ophthalmologists and 2 (6.3%) were distributed among orthoptists. Among 32 journals reviewed, 18 (56.3%) included the information of the respondents (year of graduation of the respondent, the educational level of the respondent and the demographic data). Regarding the practice’s characteristics, 5 (15.6%) included the location of the practice and 11 (34.4%) included the type of the practice. Out of 32 journals, only 17 (53.1%) included the age group in the survey. As for the scope of the test, 9 (28.1%) out of 32 included the required tests in the survey. While for the management of the patient in the practice, 11 (34.4%) out of 32 journals included the management in the survey. It was concluded that 5 scopes should be included in the survey with each modification made to suit the need of the survey. The 5 scopes were the demographic data of the respondent, the information regarding their practice, age group of the patient attended, the scope of the tests query and the management given to the patient.